PENINGKATAN DAN PENERAPAN SMK3L PADA PEMBANGUNAN PJU TENAGA SURYA DI WONOSOBO - Bagus Wahyu Utomo (Universitas Islam Indonesia, 2020)
The application of HSE culture is an integral part of national development to increase Indonesia's productivity and competitiveness. Based on data from the Manpower Social Security Organizing Agency (BPJS), throughout 2017, 1,877 claims were recorded, equivalent to Rp 41.2 billion. Construction work is considered to have a high risk of work accident rates. Occupational accident data states that 30% of work accident cases occur in the construction sector. The PJU Solar Cell construction workers in the Wonosobo area do not yet know about the safety, occupational health and environmental management system. If their workplace is safe and healthy, everyone can continue their work more effective and efficient. Conversely, if the workplace is not well organized and many dangers, damage and absenteeism are unavoidable, there is can make loss income for any workers and reduced productivity for their company. This counseling / socialization is considered successful even though it has experienced several obstacles during implementation. People who work during the project season like this have knowledge of their rights and obligations related to OSH. So that workers can better understand the risks that may occur while working.